Incidence of Surgical Site Infections and its Associated Factors: A Cross Sectional Study - Sadaf Saeed, Sara Muhammad Amin, Irshad Ahmed, Zaib Un Nisa, Jamshed Bashir, Muhammad Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the incidence of surgical site infections and its associated factors Study design: Cross sectional study Place and duration: This study was conducted at Bolan Medical Complex Hospital Quetta Pakistan from January 2020 to February 2021. Methodology: Patients who underwent general surgical procedures were included in the study. Pus or purulent discharge from the incision, together with pain, any two cardinal symptoms of inflammation were used to assess surgical site infections. For data entry and analysis, SPSS version 21 was utilized. A P-value of less than 0.05 was considered statistically significant. Results: Following the operation, 240 people were included in the current study. The average age of the study participants was 39.33 ± 2.74 years. Infections at the surgical site were found in 9.16 % (n=22) of the patients. As participants’ age increases, the surgical site infection rate rises significantly. Diabetes was found to be substantially linked to surgical site infection (P < 0.001). According to wound categorization, infection rates were higher in filthy wounds, 22.22 % versus clean wounds, 3.57%, and this difference was statistically significant (P<0.0001). Conclusion: In this study, 9.16% patients were diagnosed with surgery site infection. Age, diabetes, type, duration of surgery, kind of wound, hospital stay and presence of drain were all risk factors for surgery site infection. Keywords: Diabetes, Infection, Surgical Site infections, operation